Diagnosis Komunitas Dan Program Intervensi Dalam Upaya Penurunan Insidens Demam Berdarah Dengue di RT RW Wilayah Kerja Puskesmas Wajo Kota Baubau Sulawesi Tenggara - Denny Emilius; R. Wianti Soeryani; Shirley I. Moningkey (CV. Jasa Sukses Abadi, 2026)
Dengue Hemorrhagic Fever (DHF) is a viral infection transmitted to humans through the bite of Aedes aegypti mosquitoes. According to World Health Organization (WHO) data in 2024, approximately 5.2 million dengue cases were reported worldwide. In Southeast Asia, 648,301 dengue cases were recorded in 2019. In Indonesia, 73,518 dengue cases were reported in 2021. Meanwhile, in Baubau City, 122 dengue cases with two deaths were reported in 2025. In the working area of Wajo Primary Health Center, an increase in dengue cases was reported in January 2026, with a total of 39 cases. A mini-survey conducted at Wajo Primary Health Center revealed that community knowledge regarding dengue and its prevention through the 3M Plus strategy remains low. This activity aimed to analyze the factors contributing to the high incidence of dengue fever and to implement effective community-based interventions to reduce its incidence. This activity was conducted using a community diagnosis approach. Problem identification was carried out using the Blum health paradigm. Problem prioritization was determined through a USG method, while root cause analysis was performed using a fishbone (Ishikawa) diagram. Intervention planning was developed based on the identified root causes. The intervention consisted of health education on dengue fever and its prevention using the 3M Plus strategy. Data were collected through pre-test and post-test questionnaires, and activity evaluation was conducted using a systems approach. The health education activity, which involved 30 participants, demonstrated an increase in the mean knowledge score from 79.47 before the intervention to 96.94 after the intervention, with all participants (100%) showing improved understanding. The results of this community diagnosis activity indicate an increase in community knowledge in Lamangga Subdistrict regarding dengue fever and 3M Plus prevention. The intervention program was considered effective in enhancing community awareness and motivating preventive actions against dengue fever.